PEMBERDAYAAN PROGRAM GERAKAN SATU RUMAH SATU JUMANTIK BAGI KADER DI DESA NAMPU KABUPATEN MADIUN - Pratiwi Hermiyanti; ., Setiawan; ., Ngadino; Sulistio, Irwan (Jurnal Ilmiah Tatengkorang, 2024)
The One House One Mosquito Larva Monitor Program (G1R1J) is a dengue mosquito control program in addition to the well-known PSN Plus. The environmental conditions in Nampu Village, which have the potential to become a breeding places for Aedes mosquitoes, as well as the larva-free rate (ABJ) data which is less than 95%, make the G1R1J program necessary to be promoted in Nampu Village. The purpose of this community service is to empower mosquito larva monitor in implementing G1R1J in an effort to control Aedes mosquitoes in Nampu Village. The implementation method is in the form of counseling on mosquito bionomics, mosquito nest eradication methods and ABJ calculation practices according to G1R1J guidelines. Counseling and ABJ calculation practices were enthusiastically followed by Nampu Village mosquito larva monitor. It is hoped that the G1R1J program can be implemented with the support of the Nampu village government and the guidance of the Gemarang Community Health Center. Gerakan Satu Rumah Satu Jumantik (G1R1J) merupakan program pengendalian nyamuk DBD disamping PSN Plus yang sudah dulu lebih dikenal. Kondisi lingkungan di Desa Nampu yang berpotensi menjadi tempat perkembangbiakan nyamuk Aedes, juga data Angka Bebas Jentik (ABJ) yang kurang dari 95% menjadikan program G1R1J perlu digalakkan di Desa Nampu. Tujuan pengabdian masyarakat ini untuk memberdayakan jumantik dalam mengimplementasikan G1R1J dalam upaya pengendalian nyamuk Aedes di Desa Nampu. Metode pelaksanaan yang dilakukan berupa penyuluhan bionomik nyamuk, metode pemberantasan sarang nyamuk serta praktik penghitungan ABJ sesuai pedoman G1R1J. Penyuluhan dan praktik penghitungan ABJ diikuti secara antusias oleh Jumantik Desa Nampu. Harapan program G1R1J dapat diimplementasikan dengan dukungan pemerintah Desa Nampu dan bimbingan Puskesmas Gemarang